2004
DOI: 10.1177/095624780401600104
|View full text |Cite
|
Sign up to set email alerts
|

Participatory budgeting: a significant contribution to participatory democracy

Abstract: This paper describes participatory budgeting in Brazil and elsewhere as a significant area of innovation in democracy and local development. It draws on the experience of 25 municipalities in Latin America and Europe, selected based on the diversity of their participatory budgeting experience and their degree of innovation. The paper provides a systematic analysis of the range of experience that can be included in participatory budgeting-in terms of the level of funds being considered, the extent of control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
20

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(135 citation statements)
references
References 0 publications
0
115
0
20
Order By: Relevance
“…Participatory Budgeting The experimental setting for this work, and a driving motivation, is Participatory Budgeting, in which voters are asked to help create a government budget. Participatory budgeting has been among the most successful programs of Crowdsourced Democracy, with deployments throughout the world allocating hundreds of millions of dollars annually, and studies have shown its civic engagement benefits [5,14,15,21,22,30,32].…”
Section: Stochastic Gradient Descentmentioning
confidence: 99%
See 1 more Smart Citation
“…Participatory Budgeting The experimental setting for this work, and a driving motivation, is Participatory Budgeting, in which voters are asked to help create a government budget. Participatory budgeting has been among the most successful programs of Crowdsourced Democracy, with deployments throughout the world allocating hundreds of millions of dollars annually, and studies have shown its civic engagement benefits [5,14,15,21,22,30,32].…”
Section: Stochastic Gradient Descentmentioning
confidence: 99%
“…Methods and experiments to increase large-scale, direct citizen participation in policy-making have recently become commonplace as an attempt to revitalize democracy. Computational and crowdsourcing techniques involving human-algorithm interaction have been a key driver of this trend [5,21,22,28]. Some of the most important collective decisions, whether in government or in business, lie in high-dimensional, continuous spaces -e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other institutions around the globe exist at the local level in many countries and involve citizen participation and input. For example, "Health Councils" and "Participatory Budgeting" programs in Brazil and "Communal Councils" in Venezuela allow citizens to discuss and decide local policy decisions (Avritzer 2009;Cabannes 2004;Gott 2008;Wampler 2007). Similarly, "Town Hall" meetings in many areas of New England in the United States embrace processes that are similar to ancient Athenian democracy by allowing citizens to discuss, propose, and express policy preferences.…”
Section: A Return To Something That Once Was?mentioning
confidence: 99%
“…We will revisit the themes discussed above (understanding/knowledge building; expertise and democracy; and audiences and participants), and for each of these, we will show how the practices of PB contain both possibilities and limitations. While PB is in some ways as wonderful as proponents say [Cabannes, 2004;Souza, 2001], it does have some clear limits evident when we look through an economic lens. While PB could be and should be considered as a site for engagement with economics, discussions so far have largely focused around political questions of democracy.…”
Section: What Can Participatorymentioning
confidence: 99%